(untitled) (Manila, Philippines, 1992)
The economics of rice grain quality were studied during 1987-89. An analysis of consumer panel data in the Philippines and Indonesia, and insight into how consumers choose and value rice grain quality, are provided. Retail surveys from Bangladesh, Malaysia, the Philippines and Thailand give a comprehensive picture of the variance in rice quality and rice preference across Asia. The question how well consumer preferences are translated into incentives at farm level is addressed. Studies of rice mills and market efficiency in Indonesia and the Philippines show how well the market transmits quality signals
Keywords: Rice trade,Rice,Consumers’ preferences; Quality; Asia,Asia